Meningkatkan Rasa Cinta kepada Nabi Muhammad S.A.W. melalui Kegiatan Bersholawat di Kelas B2 RA Masjid Al – Akbar Surabaya - Sita Khusnatin Nisa; Illun Muallifah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Education plays an important role in forming good character and morals, especially in young children. In the context of Islamic education, introducing and instilling a sense of love for the Prophet Muhammad SAW is important in shaping children's religious character. One way to increase your love for the Prophet Muhammad SAW is by praying. Sholawat is a way to praise and pray for the Prophet Muhammad SAW, as well as strengthening children's spiritual connection with him and emulating the moral values ​​taught. This research was conducted in class B2 RA Al Akbar Surabaya. The aim is to explore the influence of prayer activities in increasing children's love for the Prophet Muhammad SAW. Apart from that, this research also aims to identify the most effective prayer method in fostering this love. The research results show that prayer activities carried out regularly can increase children's interest in the story of the Prophet, form positive behavior, and strengthen Islamic values ​​in children from an early age. This research contributes to the development of Islamic religious education methods in early childhood education institutions.